The Implementation of Hybrid Neuro Fuzzy Membership Function Analysis for Predicting Player Emotional Intelligence of Balinese Game Model - Suwindra, I Nyoman Putu; Darma Putra, I Ketut Gede; Sudarma, Made; Sastra, Nyoman Putra (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
This paper aims to examine the application of Neuro fuzzy membership function analysis to predict the emotions of children who like to play games. The game that has been developed is a type of game based on Balinese local wisdom, which innovates the Balinese culture-based legend I Rajapala. Rajapala who married an angel had a son named Durma. Rajapala and Durma are used as game characters that can be played on behalf of game players. Game-factor and emotional variable data were collected using a questionnaire integrated into the game system, as well as motivational data from points achieved and the use of time recorded in the game system. The data were analyzed by Sugeno Neuro Fuzzy system with hybrid and backpropagation methods. The results obtained are as follows: (1) Emotional Balinese game players can be predicted from game-factors and motivations of game players. This was shown from the FIS output (Eo) of the neuro fuzzy training analysis and the RMSE (Eo=36.8; RMSE=4.6610), the testing analysis was (Eo=33.0; RMSE=4.4528), and the checking analysis was (Eo=37.8; RMSE=4.7479) with a difference of less than 13% (training=2.72%; testing=3.0%, and checking=12.77%). In other words, if it is analyzed descriptively was (M=37.83; SD=5.3573), the output of neuro fuzzy is obtained more than 87.23%. (2) The emotional level of the child was categorized as a positive, the child's motivation was moderate and the response to the game was positive. These findings can be taken into consideration in choosing the type of game to be played in order to increase motivation and control children's emotions. Besides that, innovating games based on local wisdom is expected to preserve local Balinese culture.